An endurance time method-based fragility analysis framework for cable-stayed bridge systems under scour and earthquake. (15th July 2021) - Wei, Kai; He, Haifeng; Zhang, Jiarui; Yang, Cancan; Qin, Shunquan
Abstract: Seismic fragility assessment using structural dynamic analysis remains challenging for complex systems due to the high computational demand, such as the sea-crossing cable-stayed bridges. The paper aims to overcome this difficulty by developing an efficient seismic fragility analysis framework based on endurance time method (ETM). To demonstrate the framework for developing fragility curves, an example sea-crossing cable-stayed bridge is used as a case study. The ETM framework is validated by comparing the calculated fragility curves with those calculated by IDA framework. It is shown that the ETM is capable of significantly reducing computational effort without compromising the accuracy of fragility analysis results. The validated framework is then used to discuss the seismic fragility of sea-crossing cable-stayed bridges under scour and earthquakes. The influence of the time duration of endurance time acceleration functions (ETAFs) on the structural fragility is discussed. The influence of the time duration of ETAFs on the component fragility varies across different components, but the system fragility increases with the increasing time duration on the whole. Scour can produce either beneficial or adverse effects on the component and system seismic fragilities depending on the scour depth. Highlights: An endurance time method-based fragility analysis framework is developed for the sea-crossing cable-stayed bridge. The influence of the time duration of endurance time acceleration functions on the fragility of the sea-crossing cable-stayed bridge was studied. The effect of scour depths on the fragility of the sea-crossing cable-stayed bridge is investigated.